2020
DOI: 10.3390/app10165642
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Study Evaluating the Long Term Outcome of ChondroMimetic in the Treatment of Osteochondral Defects in the Knee

Abstract: Scaffolds are thought to be a key element needed for successful cartilage repair treatments, and this prospective extension study aimed to evaluate long-term structural and clinical outcomes following osteochondral defect treatment with a cell-free biphasic scaffold. Structural outcomes were assessed using quantitative 3-D magnetic resonance imaging (MRI) and morphological segmentation to determine the percentage of defect filling and repair cartilage T2 relaxation times, and clinical outcomes were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Several approaches have been evaluated for the cartilage regenerative outcomes including 3D bioprinting, cell-free biphasic scaffolds, mosaicplasty, MACT, and stem cell therapy [3][4][5]19,22]. Many of them giving encouraging results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches have been evaluated for the cartilage regenerative outcomes including 3D bioprinting, cell-free biphasic scaffolds, mosaicplasty, MACT, and stem cell therapy [3][4][5]19,22]. Many of them giving encouraging results.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a successful formation of a new cartilage-like tissue with a cell-density dependent zonal gradient. In another study by Berta et al [4] a cell-free biphasic scaffold (ChondroMimetic) was evaluated for long-term outcomes in the treatment of osteochondral defects. The authors observed a cartilage-like repair tissue formation and clinical improvement at 7.9 years post-implantation.…”
Section: Highlights On the Studies Published In The Present Special Issue: Emerging Therapies For Osteochondral Regenerationmentioning
confidence: 99%